FLYPAPER EFFECT PADA UNCONDITIONAL GRANT - Irham Iskandar (Muhammadiyah University Press, 2012)
This research is intended to know the influence of unconditional grants, local revenue, and GRDP to local expenditure and to detect the possibility of flypaper effect occurrences at local expenditure in West Java province. Population in this research is West Java Province and the sample consisted of 13 regency and 6 municipality. Estimates conducted by the panel regression using eviews program. The results of this research, the first show that unconditional grants significant and have positive relationships to local expenditure, local revenue has a significant and a positive relationship to local expenditure, GRDP has a significant and a negative relationship to the local expenditure. Second, the value of the coefficient of local revenue is greater than unconditional grants and both are significant. It indicates no occurrence of flypaper effect in West Java Province.